Glabellar rotation flap technique in patient with squamous cell carcinoma in right upper eyelid: case reports: Poster Presentation - Case Report - Ophthalmologist - SENYUM INDRAKILA (Majalah Oftalmologi Indonesia, 2023)
Introduction : Squamous cell carcinoma (SCC) is the second most common skin malignancy after basal cell carcinoma, with an increasing incidence worldwide. Found in various parts of the body, in the eye and periocular area, it may affect the skin of the conjunctiva, cornea, and eyelid. Surgical excision is the preferred mode of SCC treatment. After excision, reconstructive surgery is often required for the best functional and cosmetic results. Early diagnosis and treatment of tumors and follow up care for at least 5 years have a significant impact on patient survival. Case Illustration: Description of two cases squamous cell carcinoma that had undergone reconstructive biopsy and blepharoplasty procedure with glabellar rotation flap technique alone in one case and together with a cheek advancement flap in the second one. In both cases, conjunctival replacement by using lower labial mucosa. Discussion : In both cases tumor affects the margin of the upper eyelid, therefore flap reconstruction is necessary to maintain eyelid function and esthetics. The glabellar flap has the advantages of being a fast surgery, having a good vascular supply, and being able to fill deep abnormalities because it is a thick flap. A cheek lateral rotation flap was designed to avoid unnecessary facial distortion in second case. Conclusion : Glabellar rotation flap alone or together with cheek advancement flap was done to maintain function and physical aesthetic of eyelid. Additional cheek lateral rotation flap could reduce skin tension.